Turning the EU into a life insurence policy: German European policy in times of upheaval - Raphael Bossong; Kai-Olaf Lang; Barbara Lippert; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2025)
Germany's international and European policy environment is changing drastically. This necessitates a reorientation of Germany's European policy. The European Union (EU) is becoming increasingly important for Germany as a powerful community of action and should be further developed into an economic and security life insurance policy for Germany and the EU's other member states. In the coalition agreement between the CDU / CSU and the SPD, the new governing parties are claiming a pragmatic leadership role for Germany in European policy. To realise this ambition and advance key policies that are crucial for European self-determination, the new government should provide leadership that is marked by enhanced European policy coordination, grounded in an expanded partnership strategy, and aimed at strengthening the Union's overall capacity to act.
Keywords: 320; Germany's European policy; European Union (EU); policy coordination; partnership strategy; capacity to act; European Parliament (EP); NATO; Multiannual Financial Framework (MFF); migration policy